Informationsarchitekturen für künftige Energievertriebe - Gitte, Christian (KIT Scientific Publishing, 2017)
Digital products and services are changing the energy utilities deeply. In energy sales the product complexity as well as the fast-developing information technology lead to disruptive changes and new competitors. In this book a comprehensive market analysis collects systematically requirements for upcoming information architectures. Subsequently presented recommendations incorporate generalized IT enterprise architectures, new approaches for product development and useful tools.